Agreement on endoscopic ultrasonography‐guided tissue specimens: Comparing a 20‐G fine‐needle biopsy to a 25‐G fine‐needle aspiration needle among academic and non‐academic pathologists. Issue 6 (10th July 2019) - van Riet, Priscilla A.; Cahen, Djuna L.; Biermann, Katharina; Hansen, Bettina; Larghi, Alberto; Rindi, Guido; Fellegara, Giovanni; Arcidiacono, Paolo; Doglioni, Claudio; Liberta Decarli, Nicola; Iglesias‐Garcia, Julio; Abdulkader, Ihab; et al.
Abstract : Background and Aim: A recently carried out randomized controlled trial showed the benefit of a novel 20‐G fine‐needle biopsy (FNB) over a 25‐G fine‐needle aspiration (FNA) needle. The current study evaluated the reproducibility of these findings among expert academic and non‐academic pathologists. Methods: This study was a side‐study of the ASPRO (ASpiration versus PROcore) study. Five centers retrieved 74 (59%) consecutive FNB and 51 (41%) FNA samples from the ASPRO study according to randomization; 64 (51%) pancreatic and 61 (49%) lymph node specimens. Samples were re‐reviewed by five expert academic and five non‐academic pathologists and rated in terms of sample quality and diagnosis. Ratings were compared between needles, expert academic and non‐academic pathologists, target lesions, and cytology versus histological specimens. Results: Besides a higher diagnostic accuracy, FNB also provided for a better agreement on diagnosing malignancy (ĸ = 0.59 vs ĸ = 0.76, P < 0.001) and classification according to Bethesda (ĸ = 0.45 vs ĸ = 0.61, P < 0.001). This equally applied for expert academic and non‐academic pathologists and for pancreatic and lymph node specimens. Sample quality was also rated higher for FNB, but agreement ranged from poor (ĸ = 0.04) to fair (ĸ = 0.55). Histology provided better agreement than cytology, but only when a core specimen was obtained with FNB ( P = 0.004 vs P = 0.432). Conclusion: This study shows that the 20‐G FNB outperforms the 25‐G FNA needle in terms of diagnostic agreement, independent of the background and experience of the pathologist. This endorses use of the 20‐G FNB needle in both expert and lower volume EUS centers.